2018
DOI: 10.3390/ma11050864
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of 2D-Printed Edible Films for the Buccal Delivery of Diclofenac Sodium

Abstract: Printing technologies have recently emerged in the development of novel drug delivery systems toward personalized medicine, to improve the performance of formulations, existing bioavailability patterns, and patients’ compliance. In the context of two-dimensional printing, this article presents the development of buccal films that are designed to efficiently deliver a class II compound (diclofenac sodium), according to the Biopharmaceutics Classification System (BCS), to the oral cavity. The preparation of drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
0
12
0
4
Order By: Relevance
“…However, the 5-and 9-printed films presented lower vitamin dosing than expected, when compared to the 1-printed film. The disproportionate increase in dosing of inkjet-printed formulations, in relation to the number of printing passes, has been previously reported and associated with the shear forces that develop during the feeding process of the printer [49,50]. The conveyance of the edible sheets to the printing zone occurs upon traction of the substrate by the drive rollers of the device.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, the 5-and 9-printed films presented lower vitamin dosing than expected, when compared to the 1-printed film. The disproportionate increase in dosing of inkjet-printed formulations, in relation to the number of printing passes, has been previously reported and associated with the shear forces that develop during the feeding process of the printer [49,50]. The conveyance of the edible sheets to the printing zone occurs upon traction of the substrate by the drive rollers of the device.…”
Section: Discussionmentioning
confidence: 88%
“…Two broad endotherm peaks were detected in the temperature range of 70-150 • C and 190-250 • C for the plain sugar sheet and the formulations. These peaks are attributed to the evaporation of water and to the endothermic patterns of maltodextrin and sugar monosaccharides [50]. In the FTIR spectrum of THCl, characteristic peaks at 1650 cm −1 and 1600 cm −1 corresponded to the stretching bonds of C = N and aromatic C = C respectively [53] and peaks at 1347 cm −1 and 1438 cm −1 corresponded to the stretching modes of CH group of the pyrimidine ring [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, it was also shown that the bigger the drop volume the higher is the crystalline proportion because small drops dry faster and the drug substance has less time for crystallization. The more printing passes the higher was the amorphous ratio due to the increasing amount of propylene glycol and higher solvation of the drug [103,106]. With increased drug content, the recrystallization rate can increase and drug crystals can be formed on the top of the oromucosal films [95].…”
Section: Pharmaceutical Inkjet Printingmentioning
confidence: 99%
“…From the final selection of APIs, diclofenac [36], indomethacin [32,37], montelukast [38] and prednisolone (frequently dispensed instead of prednisone, as listed in Table 3) [39] have been already successfully printed using the inkjet technique on ODFs or transparency sheets. In the case of montelukast and prednisolone, the therapeutic dose was achieved, however, in the case of diclofenac and indomethacin, the printed dose remained too low.…”
Section: Discussionmentioning
confidence: 99%